2010
DOI: 10.1348/000709909x466334
|View full text |Cite
|
Sign up to set email alerts
|

Teacher expectations and perceptions of student attributes: Is there a relationship?

Abstract: This study adds weight to the argument that class level expectations are important for student learning. Teacher moderators appear to relate to differing teacher beliefs and attributes (mediators) and hence may lead to variance in the instructional and socio-emotional climate of the classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
97
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(113 citation statements)
references
References 29 publications
1
97
3
6
Order By: Relevance
“…The empirical evidence for an association between teachers' perceptions of student attributes and their expectations for students' future academic performance is rather limited, but there are several prior studies that have focused on this subject. Teachers' expectations for the academic achievement of primary school students have been found to be positively related to students' perceived assertiveness, independence (Alvridez and Weinstein 1999;Bonvin and Genoud 2006;Rubie Davies 2010), and self-confidence (Driessen 2006;Rubi-Davies 2010). These studies indicate that teachers tend to have higher expectations of a student if they perceive the student as independent and more confident.…”
Section: Teacher Perceptions Of Student Attributes and Expectationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The empirical evidence for an association between teachers' perceptions of student attributes and their expectations for students' future academic performance is rather limited, but there are several prior studies that have focused on this subject. Teachers' expectations for the academic achievement of primary school students have been found to be positively related to students' perceived assertiveness, independence (Alvridez and Weinstein 1999;Bonvin and Genoud 2006;Rubie Davies 2010), and self-confidence (Driessen 2006;Rubi-Davies 2010). These studies indicate that teachers tend to have higher expectations of a student if they perceive the student as independent and more confident.…”
Section: Teacher Perceptions Of Student Attributes and Expectationsmentioning
confidence: 99%
“…These studies indicate that teachers tend to have higher expectations of a student if they perceive the student as independent and more confident. Moreover, teachers' expectations were found to be associated with their perceptions of the students' social behavior in the classroom (Bennet et al 1993;Driessen 2006;Hecht and Greenfield 2002;LaVoie and Adams 1973) and engagement (Kelly and Carbonaro 2012;Rubie-Davies 2010). For example, in an experimental study among 350 teachers, LaVoie and Adams (1973) found that children for whom teachers perceived low grades in personal and social growth, work habits, and attitudes, were predicted to have less ability and lower aspirations than children with acceptable conduct.…”
Section: Teacher Perceptions Of Student Attributes and Expectationsmentioning
confidence: 99%
See 3 more Smart Citations